The methodology for evaluating accessibility as a tool for increasing social responsiveness of urban landscapes in Singapore - Gintaras Stauskis (Acta Scientiarum Polonorum. Formatio Circumiectus)
Accessibility of public environment make immense impact on active participation of all citizens in different spheres of public life. Quality of access to urban landscapes and buildings for all citizens gains especial importance in the context of recent demographic trends in the developed countries, as ageing communities, decreasing birth rates and continuing urbanisation of natural environment. Creation of a more responsive urban environment is the instrument to facilitate social integration of people into active public life, especially for the ones with limited physical abilities, instead of sheltering them from a society by extending social services. The author presents a research-based methodology for analyzing and evaluating accessibility in public areas of a big city. The originality of the method lays in empowering the disabled persons to play the active role of experts in measuring and evaluating accessibility according the developed assessment tool. The used methodology allows evaluating accessibility on different urban scales: in urban landscapes, in buildings, and in their interiors. The presented case study performed in Singapore explores the quality of access that people have to public spaces, metro stations, hotels and café. As a result, the author presents recommendations for improving accessibility in the city by improving the quality of urban environment and architectural design of buildings, updating the building regulations, as well as construction and maintenances of open spaces and buildings. The results of this research provide the comprehensive action plan for eliminating barriers in the specific Singapore’s environment and in the other cities. Conclusions present the model of coherent accessibility monitoring tool and improvement programme that facilitates creation of a socially responsive urban environment.